2022
DOI: 10.3847/1538-4357/ac86c9
|View full text |Cite
|
Sign up to set email alerts
|

KIC 2857323: A Double-mode High-amplitude δ Scuti Star with Amplitude Decline of the First Overtone Mode

Abstract: We investigate the pulsating behavior of KIC 2857323 using high-precision observations from the Kepler mission. Fourier analysis of 4 yr time-series data reveals five independent frequencies for the light variation. Among them, two strong frequencies f 1 and f 3 with a period ratio of 0.774 identify this star as a double-mode (i.e., the fundamental mode F0 and first overtone mode F1) high-amplitude δ Scuti star (HADS). Seismic modeling using the two radial modes F0 and F1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…These results show that HADS should be located in the post-MS evolutionary stage. However, some works show that some HADS can also be located in the terminal-age main-sequence (TAMS) or even MS (see, e.g., Bowman et al 2021;Sun et al 2021;Lv et al 2022;Yang et al 2022), although the observed period variations are inconsistent with (always significantly greater than) the theoretical model predictions in these works.…”
Section: Introductionmentioning
confidence: 96%
“…These results show that HADS should be located in the post-MS evolutionary stage. However, some works show that some HADS can also be located in the terminal-age main-sequence (TAMS) or even MS (see, e.g., Bowman et al 2021;Sun et al 2021;Lv et al 2022;Yang et al 2022), although the observed period variations are inconsistent with (always significantly greater than) the theoretical model predictions in these works.…”
Section: Introductionmentioning
confidence: 96%
“…However, it is very difficult to identify them, since the asymptotic theory is invalid due to the low radial order. Conversely, identification of the modes in HADS stars is clear and straightforward, because HADS stars typically pulsate in the radial fundamental mode and/or low-overtone radial modes (McNamara 2000), such as for VX Hydrae (Xue et al 2018), GSC 4552-1498 (Sun et al 2021), KIC 2987323 (Yang et al 2022), and TIC 448892817 (Lv et al 2022). The pulsation of δ Scuti stars contains both radial and nonradial p modes, signifying the potential to investigate the stellar envelope.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that most δ Sct stars have amplitude modulations accompanied by period variations, representing different evolutionary stages . Thus, the identification of modes of δ Sct stars is an important research focus in asteroseismology (Balona & Evers 1999;Lv et al 2022;Yang et al 2022). Mode identification is performed by analyzing the light curves (LCs) of δ Sct stars (Breger et al 1993).…”
Section: Introductionmentioning
confidence: 99%